The Influence of Pakpak Culture Based on Guided Discovery Learning Model in Mathematical Communication Ability and Self Confidience of Students in SD Negeri No. 030277 Teladan, Sidikalang Districts, Dairi Regency - Erentiana Prinita Sinaga; KMS. M. Amin Fauzi; Waminton Rajagukguk (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
In fact, the implementation of the teaching-learning process does not train and develop students' communication skills to cause interaction between students, such as working together, expressing ideas, asking questions, and responding to questions / opinions of other students. The teachers have applied the discussion learning model, but this is done with a direct learning model. During the discussion, the teacher only gives a number of assignments to students which contain almost all of the material without giving instructions, so that the students' thinking patterns do not develop and are not stimulated to think critically. This research was conducted at SD Negeri No.030277 Teladan Sidikalang, Sidikalang District, Dairi Regency. The population in this study was all fifth grade students of SD Negeri No.030277 Teladan Sidikalang which consisted of 3 classes totaling 91 students. Class VA as many as 31 students, class VB as many as 30 students, and class V-C as many as 30 students. There is a significant influence between learning (guided discovery learning and direct learning) on students' mathematical communication skills. The effect of the independent variable on changes in the dependent variable is 31.2%, while the remaining 68.8% is influenced by other variables. There is a significant influence between learning (guided discovery learning and direct learning) on students' self confidence. The effect of independent variables on variable changes is 9.6%, while the remaining 90.4% is influenced by other variables.